2007
DOI: 10.1007/s10086-006-0837-9
|View full text |Cite
|
Sign up to set email alerts
|

Climatic responses of tree-ring widths of Larix gmelinii on contrasting north-facing and south-facing slopes in central Siberia

Abstract: An analysis was performed of the climatic responses of the radial growth of Larix gmelinii (Rupr.) Rupr. on contrasting north-and south-facing slopes in Tura, central Siberia. We developed chronologies of tree-ring width for four plots, designated north-upper, north-lower, south-upper and south-lower. Both residual and standard chronologies of tree-ring widths exhibited a significant positive correlation with temperature from the end of May until the early June in all four plots. The chronologies of ring width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
1
15
0
2
Order By: Relevance
“…Non-significant (NS) indicates a probability . 0.05. production of cells to be differentiated in summer and longer durations of xylogenesis (Kujansuu et al, 2007;Rossi et al, 2008b;Lupi et al, 2010). Moreover, the low temperatures in early spring could prevent high rates of cell division from being achieved even if complete snowmelt has occurred (Deslauriers et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Non-significant (NS) indicates a probability . 0.05. production of cells to be differentiated in summer and longer durations of xylogenesis (Kujansuu et al, 2007;Rossi et al, 2008b;Lupi et al, 2010). Moreover, the low temperatures in early spring could prevent high rates of cell division from being achieved even if complete snowmelt has occurred (Deslauriers et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rossi et al (2008) indicated that variations in the period of xylem growth might be the cause of age-dependent responses to climate. In addition, changes in hormone balances that govern cambial growth, shifts in the ratio of photosynthetic to non-photosynthetic tissues, and any modification in the mechanisms of absorption and translocation of water and metabolites that occur during ageing (Duff and Nolan 1953;Kozlowski 1971;Kramer and Kozlowski 1979;Harcombe 1987) could affect the response of tree-ring growth to climate.…”
Section: Age-dependent Climate-growth Responsementioning
confidence: 98%
“…Thus, the responses of radial growth of larch trees to climatic change have significant influence on the global carbon balance (Kujansuu et al 2007). Several tree-ring studies have shown that Dahurian larch appears to be very sensitive to climatic change allowing it to be a good study species in dendroclimatic studies (Naurzbaev et al 2002;Kirdyanov et al 2003;Wang et al 2005a;Kujansuu et al 2007). However, very few studies have tested whether climate-growth responses are stable across different larch age classes and sites.…”
Section: Introductionmentioning
confidence: 99%
“…)和利 用落叶松树轮宽度指数重建夏季温度变化 (Chen et al, 2013), 然而对气候变暖后相同生境的落叶松 生长特性和模式的南北差异研究很少; 最后, 关于 落叶松相关种属的生长与气候变化关系的研究多集 中于与我国临近的西伯利亚地区 (Andreu et al, 2007;Kujansuu et al, 2007;Sano et al, 2009;Wu et al, 2012;Bryukhanova et al, 2013) (Fritts, 1976;吴祥定, 1990), 并用精度为 化越敏感 (Fritts, 1976;Cook & Kairiukstis, 1990) 图4 落叶松年轮宽度指数与温度的相关关系。A, 大兴安岭南部落叶松年轮宽度指数与温度的相关系数。B, 大兴安岭中部 落叶松年轮宽度指数与温度的相关系数。 C, 大兴安岭北部落叶松年轮宽度指数与温度的相关系数。P6, 前一年的6月; P7, 前一年的7月; P8, 前一年的8月; P9, 前一年的9月; P10, 前一年的10月; P11, 前一年的11月; P12, 前一年的12月; BG, 生长季前; CG, 当年生长季; PA, 上年秋季; PG, 上年生长季; PW, 上年冬季; T m , 月/季度平均温度; T max , 月/季度平均最 高温度; T min , 月/季度平均最低温度。 Fig. 4 Correlations between tree-ring width index in Larix gmelinii and temperature.…”
unclassified